Architectural acoustics illustrated - Ermann, Michael (Michael A.) (Hoboken, New Jersey : Wiley, 2015)
'Translates the quantitative and qualitative content of acoustics into the graphic language of architecture and outlines the best practices for limiting or mitigating noise in buildings'--
Includes bibliographical references and index.
Keywords: Architectural acoustics; Architectural acoustics -- Pictorial works